In Vitro Cytotoxic Activity Of Lannea Coromandelica Leaf Extract On Artemia Salina Leach As A Model For Anticancer Screening - Haryanto Haryanto; Alyssa Putri Saldi; Nurul Istiqamah; Andi Aisyah Fitria Pratiwi; Nurun Nazhifah Syam; Nayla Ratu Mardiana; Zulkifli Zulkifli (CV. AFDIFAL MAJU BERKAH, 2026)
Cancer and non-communicable diseases are a growing global health crisis, prompting intensive investigation of medicinal plants as sources of novel bioactive compounds. Lannea coromandelica (Houtt.) Merr., locally known as Kayu Jawa, is a tropical tree of the Anacardiaceae family traditionally used in traditional Asian medicine, but its leaf fraction has not been systematically evaluated for its cytotoxic potential. This study aimed to determine the lethal concentration (LC50) of L. coromandelica leaf ethanol extract against Artemia salina nauplii using the Brine Shrimp Lethality Test (BSLT). A true experimental design was used, with ten nauplii exposed to seven concentration groups (negative control, 10, 100, 500, 1,000, 5,000, and 10,000 ppm) in triplicate for 24 hours. Mortality data were analyzed using the Reed and Muench interpolation method and probit regression analysis. The results showed a clear concentration-dependent mortality pattern, with mortality of 21.42% at 10 ppm and 84.61% at 100 ppm, reaching 100% from 500 ppm and above. The LC50 was 3.53 ppm by the Reed and Muench method and 4.1629 ppm by probit analysis, both classified as highly toxic (LC50 < 30 ppm) according to Meyer et al. with a toxic category. The high cytotoxic activity is consistent with the presence of flavonoids, phenolics, triterpenes, and saponins in the leaf extract. These findings establish a strong toxicological basis and support further investigation of L. coromandelica leaf extract as a potential anticancer agent.